Perceived barriers to multiprofessional team briefings in operating theatres: A qualitative study - Fruhen, Laura; Carpini, J.A.; Parker, Sharon; Leung, Y.; Flemming, A.F.S. (BMJ PUBLISHING GROUP, 2020)
Objectives This study investigates perceived barriers towards the implementation of multiprofessional team briefings (MPTB) in operating theatres, as well as ways to overcome these perceived barriers. Previous research shows that MPTB can enhance teamwork and communication, but are underused in operating theatres. By adopting a multilevel systems perspective, this study examines perceived barriers and solutions for MPTB implementation. Design Participants completed open-ended survey questions. Responses were coded via qualitative content analysis. The analysis focused on themes in the responses and the systems level at which each barrier and solution operates. Setting Four tertiary hospitals in Australia. Participants 103 operating theatre staff, including nurses, surgeons, anaesthetists, technicians and administrators. Results Participants identified barriers and solutions at the organisational (15.81% of barriers; 74.10% of solutions), work group (61.39% of barriers; 25.09% of solutions) and individual level (22.33% of barriers; 0% of solutions). Of all the perceived barriers to MPTB occurrence, a key one is getting everyone into the room at the same time. Matching of perceived barriers and solutions shows that higher systems-level solutions can address lower level barriers, thereby showing the relevance of implementing such wider reaching solutions to MPTB occurrence (including work practices at occupational level and above) as well as addressing more local issues. Conclusions Successful MPTB implementation requires changes at various systems levels. Practitioners can strategically prepare and plan for systems-based strategies to overcome barriers to MPTB implementation. Future research can build on this study's findings by directly examining higher systems-level barriers and solutions via detailed case analyses.